2001
DOI: 10.1002/cjoc.20010191206
|View full text |Cite
|
Sign up to set email alerts
|

Studies on chemistry and immuno‐ modulating mechanism of a glycoconjugate from Lycium barbarum L.

Abstract: The detailed structure of an 0-glycan derived from the fruit of L y c h bmbmum L. was elucidated based on glycosidic linkage analysis, complete and partial acid hydrolysis, 'H-NMR and u C N M R spectroscopy. According to the experiments, the carbohydrate was in the form of pdysacchride ( a r a b i i a c t a n ) chains with highly branched 3,4-gaktans and terminal arabiiwfumnasyl Substitwnts. and its glycan were investigated using tritium thymidine incorm b t y s h i f f assay ( M A ) . The results suggested th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 12 publications
0
28
1
Order By: Relevance
“…␣-l-Rhamnopyranosyl residues also existed as terminal sugars. The structural features reported here contradict earlier reports that Wolfberry AGPs carry a backbone of (1 → 4)-linked ␤-dgalactopyranosyl residues (Huang et al, 1999;Peng, Huang, et al, 2001) and confirm the assignment of Zhang and Zhang (2007) that the backbone is a (1 → 3)-␤-d-galactan.…”
Section: Concluding Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…␣-l-Rhamnopyranosyl residues also existed as terminal sugars. The structural features reported here contradict earlier reports that Wolfberry AGPs carry a backbone of (1 → 4)-linked ␤-dgalactopyranosyl residues (Huang et al, 1999;Peng, Huang, et al, 2001) and confirm the assignment of Zhang and Zhang (2007) that the backbone is a (1 → 3)-␤-d-galactan.…”
Section: Concluding Discussioncontrasting
confidence: 59%
“…Glycoconjugates in the form of arabinogalactanproteins (AGPs) were identified, confirming several previous reports of these molecules in Wolfberry fruit. In two of these publications (Huang, Tian, & Zheng, 1999;Peng, Huang, Qi, Zhang, & Tian, 2001) it was reported that the glycoconjugates LbGp3 and LbGp4 were AGPs containing a (1 → 4)-linked galactopyranan backbone frequently substituted at O-3 with highly branched side chains terminated predominantly by arabinofuranosyl residues. The authors pointed out the novelty of this structure, as most known plant-derived AGPs carry a (1→ 3)-linked galactopyranan backbone substituted at O-6 with side chains containing additional galactopyranosyl residues as well as arabinofuranosyl residues.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, LBP is extracted from the edible Chinese herb, Lycium barbarum. Previous studies have shown that LBP could enhance the proliferation of splenocytes in mice [34,35], activate macrophages [36], and promote both the phenotypic and functional maturation of DC [37]. Besides, LBP also has various other biological activities, such as neuroprotective effects [38,39], radioprotective activity [40], cardioprotective activity [41], and hepatoprotective effects [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…There are evidences that LBP act through enhanced expression of various cytokines and transcription factors. The protein polysaccharide complex LbGp4 stimulates the expression of nuclear factor κB (NfκB) and activator protein 1 (AP-1) [15]. LBP3 was shown to increase the expression of interleukin-2 (IL-2) and tumor necrosis factor-α (TNF-α) at the mRNA and protein levels in cultures of human peripheral blood mononuclear cells [44].…”
Section: Pharmacological Propertiesmentioning
confidence: 99%
“…LBP have been shown in several studies to promote splenocyte proliferation in vitro [14,15,43]. There are evidences that LBP act through enhanced expression of various cytokines and transcription factors.…”
Section: Pharmacological Propertiesmentioning
confidence: 99%